2002
DOI: 10.2754/avb200271040451
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Ions on Ruminal Enzyme Activities

Abstract: In vitro incubation experiments were conducted to evaluate the influence of several metal ions on urease, alanine aminotransferase (ALT), aspartate aminotransferase (AST), gammaglutamyltransferase (GGT) and glutamate dehydrogenase (GDH) enzyme activities of rumen fluid. Rumen fluid was collected from eight fistulated ewes and strained through a cheesecloth. Magnesium, copper and cadmium were each added to 10 ml of rumen fluid to obtain final concentrations of 5 mmol . l -1 . After the addition of each metal io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Sensitivity of rumen bacteria to heavy metals ranges in large scale depending on bacterial species and conditions with consequences on their metabolic activity (Forsberg 1978;Legáth et al 1990;Lauková 1994;Lenártová et al 1998;Faixová & Faix 2002). In comparison with our resultsE.…”
Section: Discussionsupporting
confidence: 76%
“…Sensitivity of rumen bacteria to heavy metals ranges in large scale depending on bacterial species and conditions with consequences on their metabolic activity (Forsberg 1978;Legáth et al 1990;Lauková 1994;Lenártová et al 1998;Faixová & Faix 2002). In comparison with our resultsE.…”
Section: Discussionsupporting
confidence: 76%
“…Hence, several other additives that could be used to manipulate fermentation of dietary substrates by rumen microbes are currently under study. Various metal ions could affect rumen fermentation (Martínez et al, 1970;Spears and Hatf ield, 1978;Rodríguez et al, 1995;Arelovich et al, 2000;Faixova and Faix, 2002). Previous research indicated that dietary addition of 250 to 400 mg Zn kg -1 DM to low-quality forage altered rumen fermentation by retarding ammonia accumulation and increasing molar proportions of propionate (Arelovich et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa (Medicago sativa L.) hay and barley (Hordeum vulgare L.) grain are common ingredients used for growingfinishing diets in beef cattle. Animal performance on this type of diet could be increased by the addition of Zn in the diet (Arelovich et al, 2000;Faixova and Faix, 2002;Bateman II et al, 2004). One of the advantages of using Zn as an additive is that various inorganic Zn salts can be easily obtained in the market, and usually they have a lower cost when compared to monensin or similar feed additives.…”
Section: Introductionmentioning
confidence: 99%
“…However, high levels of Zn in lambs could have protecting effect from Cu depletion originated in high levels of Cd in the diet. Also Zn not retained in the animal and excreted could be a potential hazard in areas that are already contaminated by heavy metals (Faixova and Faix, 2002). Any way in this study the levels of Zn supplied by treatments were much lower than previously studied when proposed as an additive to manipulate rumen fermentation.…”
Section: Zinc Effects On Rumen Parametersmentioning
confidence: 60%
“…A recent review discusses progress in decreasing rumen methane through different additives by rumen microbial manipulation (Kobayashi, 2010). Some essential elements could also impact on rumen microbial fermentation as well (Martinez and Church, 1970;Spears and Hatfield, 1979;Rodriguez et al, 1995;Arelovich et al, 2000;Faixova and Faix, 2002;Arelovich et al, 2008;Richter, 2011). Previous research indicated that dietary addition of 250 to 400 mg Zn kg −1 DM to low-quality forage supplemented with urea retarded ammonia accumulation and increased molar proportions of propionate in beef cattle (Arelovich et al, 2000).…”
Section: Introductionmentioning
confidence: 99%